Gerakan Sedekah Sampah dan Minyak Jelantah Sebagai Upaya Peningkatan Kesadaran Lingkungan Masyarakat Desa Tembok Luwung Kecamatan Adiwerna Kabupaten Tegal - Koidin, Mohammad; Rizza, Bakhtiar; Alfarez, Rafi; Fatikha, Laila Nur; Darojah, Rofiatun; Multajimah, Silvi Azkia (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2023)
The Sedekah Garbage and Used Cooking Oil movement is a campaign effort carried out to instill changes in people's behavior to process waste with a religious approach. This study aims to determine the implementation of the Garbage Alms Movement and used cooking oil as an effort to build cultural awareness of the environment. In this study the method used is qualitative with a case study approach. Data analysis techniques use the Miles and Huberman models. Data collection was carried out by means of observation, interviews and documentation. The theoretical foundation in this study is the environmental theology theory of Seyyed Hossein Nasr. The results of the research are the implementation of the Garbage Alms Movement and used cooking oil including outreach, collection of waste from the community, sorting, weighing and reporting. Through the implementation of the Alms Movement and Waste Used Oil Movement, there are types of environmental awareness, namely mechanical awareness and organic awareness. Movement Implementation. Garbage Alms can build environmental awareness in the form of benefits received by people in need, namely the provision of social assistance, and economic empowerment.